Base Nacional Comum Curricular e o Documento Curricular do Tocantins, dos anos iniciais do ensino fundamental: um olhar a partir da pedagogia histórico-crítica - Oliveira, Marília Rodrigues de (Universidade Federal do Tocantins, 2025)
This article is the result of readings and discussions about the curriculum from the perspective of historical-critical pedagogy. The methodology of this theory is based on historical-dialectical materialism and brings a different vision from other counter- hegemonic pedagogical theories. In this sense, to explain the theory and carry out the proposed analysis we used authors such as Julia Malanchen (2020), Paulino José Orso (2023), Dermeval Saviani (2013), Marta Regina (2021). This article uses, among others, bibliographical research and a qualitative approach. The central objective of this work is to analyze the Tocantins Curricular Document for the initial years based on discussions of Historical-Critical Pedagogy. As specific objectives we have the following: deal with the foundations of Historical-Critical Pedagogy; draw an overview of the Tocantins Curricular Document based on the National Common Curricular Base; know the Tocantins Curriculum Document for Elementary Education. We understand that, in the same way as the National Common Curricular Base, the Tocantins Curricular Document, is based on Competence Pedagogy and this does not seek to give autonomy, quite the contrary, it seeks to mold it to the capitalist world, preparing it for the job market and making it individualistic, which for the working class collective does not favor the transformation of its reality.